Bacterial Bloodstream Infections in HIV-infected Adults Attending a Lagos Teaching Hospital (Journal of Health, Population and Nutrition, 2010)
An investigation was carried out during October 2005-September 2006 to determine the prevalence of bloodstream infections in patients attending the outpatient department of the HIV/AIDS clinic at the Lagos University Teaching Hospital in Nigeria. Two hundred and one patients-86 males and 115 females-aged 14-65 years were recruited for the study. Serological diagnosis was carried out on them to confirm their HIV status. Their CD4 counts were done using the micromagnetic bead method. Twenty mL of venous blood sample collected from each patient was inoculated into a pair of Oxoid Signal blood culture bottles for 2-14 days. Thereafter, 0.1 mL of the sample was plated in duplicates on MacConkey, blood and chocolate agar media and incubated at 37 °C for 18-24 hours. The CD4+ counts were generally low as 67% of 140 patients sampled had